Novel assessments of systemic calcification propensity. Issue 4 (July 2016) - Pasch, Andreas
Abstract : Purpose of review: Blood is a biological fluid, which controls the precipitation of calcium and phosphate and transports mineral debris. This review presents and discusses the current concepts and novel assessment methods of systemic calcification propensity in blood. Recent findings: Calcium and phosphate combine with calcification-inhibiting proteins, mainly fetuin-A, to form amorphous calcium phosphate-containing primary calciprotein particles (CPPs). These nanosized mineral-protein clusters undergo spontaneous transformation to secondary CPP, which contain crystalline calcium phosphate. Two recently developed methods assess complementary aspects of the calcification propensity of serum. The CPP-fetuin-A method determines the amount of sedimentable fetuin-A, whereas the T50 -Test determines the transformation time point T50 from amorphous to crystalline CPPs in artificially supersaturated serum. Clinical studies in renal patients have already demonstrated close associations of the CPP-fetuin-A method with all-cause mortality, severity of coronary calcification and aortic stiffness, and of the T50 -Test with cardiovascular and all-cause mortality, renal graft failure and aortic stiffening. Summary: Systemic calcification propensity can be assessed by two novel methods providing complementary information about the status and performance of the humoral calcification-regulating system in serum. These tests may help guide better patient care in the future with the use of more individualized therapies.